Axenic Procyclic Culture of L. tropica and L. donovani in Culture of FBS-free Medium - M. Mosa, Fatema; A. Salman , Husam; Z. Ali, Hayder (Iraqi Journal of Science, 2023)
Leishmania causes disease ranging from self-healing cutaneous to fatal visceral leishmaniasis (VL). Leishmaniasis is reported endemic in 88 countries, including Iraq, in which 82% in low-income countries. The diseases develop following the bite of sand flies injecting Leishmania promastigotes into skin. Promastigotes transform into amastigotes in vivo multiplying within macrophages. In this study we have investigated the ability of axenic procyclic promastigotes of cutaneous Leishmania tropica and visceral Leishmania donovani survive in M199 media with or without Fetal Bovine Serum (FBS) added. Three time incubation periods were adopted (24, 48 and 72) hours and the results showed that L. tropica was able to survive and multiply in both FBS-medium and FBS-free medium, while L. donovani showed significant decrease in surviving in the FBS-free medium at day three of follow up. Such results may indicate the difference in Leishmania species requirements in growth culture in vitro.